Human herpesvirus 8 K14 protein mimics CD200 in down-regulating macrophage activation through CD200 receptor. - Foster-Cuevas, M; Wright, G; Puklavec, M; Brown, M; Barclay, N (2004)
Many viral proteins limit host immune defenses, and their genes often originate from their hosts. CD200 (OX2) is a broadly distributed cell surface glycoprotein that interacts with a receptor on myeloid cells (CD200R) that is implicated in locally preventing macrophage activation. Distant, but recognizable, homologues of CD200 have been identified in many herpesviruses and poxviruses. Here, we show that the product of the K14 open reading frame from human herpesvirus 8 (Kaposi's sarcoma-associated herpesvirus) interacts with human CD200R and is expressed at the surfaces of infected cells solely during the lytic cycle. Despite sharing only 40% primary sequence identity, K14 and CD200 interacted with CD200R with an almost identical and low affinity (K(D) = 0.5 microM), in contrast to other characterized viral homologue interactions. Cells expressing CD200 or K14 on the cell surface were able to inhibit secretion by activated macrophages of proinflammatory cytokines such as tumor necrosis factor alpha, an effect that could be specifically relieved by addition of monoclonal antibodies and soluble monomeric CD200 protein. We conclude that CD200 delivers local down-modulatory signals to myeloid cells through direct cell-cell contact and that the K14 viral homologue closely mimics this.